OVERVIEW OF THE SLEEP QUALITY OF PREGNANT WOMEN TRIMESTER III - Wenny Indah Purnama Eka Sari; Kurniyati; Yusniarita (Poltekkes Kemenkes Bengkulu, 2023)
Pregnancy is a long adaptation process. At the end of pregnancy there is a decrease in the quality of sleep in third trimester pregnant women due to changes in physiological and psychological adaptation. The quality of sleep for pregnant women has an effect on the condition of the mother during pregnancy. The aim of the study was to describe the sleep quality of third trimester pregnant women in the Working Area of the Perumnas Public Health Center, Rejang Lebong Regency in 2023. This research is a descriptive type of research. Research sample for third trimester pregnant women was selected by simple random sampling. Research time in May – June 2023. The research sample Determination of the number of samples using the Solvin formula amounted to 68 respondents. Data analysis describes the characteristics of each variable with a percentage. Research resultshows that almost all respondents are aged 20-35 years (76.5%), more than half are primigravida respondents (72.1%), more than half are highly educated (67.6%) and more than half are not working (69. ,1%), gdescription of the quality of sleep almost all respondents 82.4% have poor sleep quality. The decrease in the quality of sleep in the third trimester of pregnant women occurs due to changes in physiological and psychological adaptation. Physiological changes experienced by pregnant women, due to increasing gestational age such as abdominal enlargement, anatomical changes and hormonal changes, while psychological changes are caused by anxiety and worry before delivery. Midwives can provide complementary care to address complaints of sleep disturbances for pregnant women at the end of the trimester so that pregnant women can improve the quality of sleep for pregnant women